2011
DOI: 10.1080/02699931.2011.588690
|View full text |Cite
|
Sign up to set email alerts
|

Examining the structure of emotional intelligence at the item level: New perspectives, new conclusions

Andrew Maul

Abstract: Despite twenty years of research, many unknowns remain regarding the Mayer-Salovey (e.g., 1997) model of emotional intelligence (EI) and the validity of tests that have been designed to measure it. Evidence relevant to the internal structure of EI has come mainly from factor-analytic studies of the MSCEIT and the MEIS, utilising parcelled task scores rather than individual test items. This approach has several deficiencies: in addition to the loss of item-level information, it results in an insufficient number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…Nonetheless, we should admit that the AEI framework has shown advantages (Fiori, 2009), but the theoretical AEI framework might be better explained using the Cattell-Horn-Carroll mental abilities model and emotional appraisal theory (Roberts et al, 2016) since measures of AEI only have assessed a part of the emotional intelligent behavior, the emotional conscious part (Fiori, 2009;Fiori and Antonakis, 2011). Hence, AEI measures still lack information about how extent emotions, AEI measures, and intelligence are related (Roberts et al, 2006;Maul, 2012). Especially for under-17-year-old samples, it would a possibility to build a TEI instrument according to the AEI theoretical foundations (Billings et al, 2014;Davis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, we should admit that the AEI framework has shown advantages (Fiori, 2009), but the theoretical AEI framework might be better explained using the Cattell-Horn-Carroll mental abilities model and emotional appraisal theory (Roberts et al, 2016) since measures of AEI only have assessed a part of the emotional intelligent behavior, the emotional conscious part (Fiori, 2009;Fiori and Antonakis, 2011). Hence, AEI measures still lack information about how extent emotions, AEI measures, and intelligence are related (Roberts et al, 2006;Maul, 2012). Especially for under-17-year-old samples, it would a possibility to build a TEI instrument according to the AEI theoretical foundations (Billings et al, 2014;Davis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(DeMars, 2012, p. 105) Furthermore, overlooking dependence among items can lead to inappropriate conclusions about the internal structure of tests. Maul (2012), after modeling LID in the Mayer-Salovey-Caruso Emotional Intelligence Test (Mayer, Salovey, & Caruso, 2002) concluded that the multidimensional structure commonly hypothesized for the test cannot be supported and a unidimensional model is just as good to describe the construct. Along the same lines, Wang, Cheng, and Wilson (2005) found that when LID is modeled the correlations between latent traits substantially drop, which obviously presents a dramatically different structure for the latent trait.…”
Section: Discussionmentioning
confidence: 98%
“…An assumption of measurement models is that correlations among items should be due only to the common latent trait. In a recent study [24] it was suggested to model variance in item response according to the stimulus material, so as to account for shared variance that depends on the structure of the test rather than on the latent trait. The idea is that if one person judges a picture as expressing a great extent of joy, then as a consequence this person will judge the picture as expressing very little sadness.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire showed good precision in discriminating individuals along the trait and high information values for most items. Regarding ability EI, Maul [24] conducted an item analysis of the MSCEIT to investigate the hypothesized structure of the test. He found no strong evidence for preferring a unidimensional model over a four-dimensional model of EI when controlling for facet-related variance.…”
Section: An Irt Approach To the Msceitmentioning
confidence: 99%